Constructing Promotional Meaning Through Code-Mixing and Visual Elements in Roti’O Indonesia’s Instagram Content - Tri Ramadani; Erlan Aditya Ardiansyah; Fourus Huznatul Abqoriyyah (GLENS: Global English Insights Journal, 2026)
This study aims to examine how code-mixing and visual elements work together in constructing promotional meaning. The use of code-mixing and visual elements in digital promotion has become increasingly widespread as a marketing communication strategy to attract audiences and build a modern product image. However, studies integrating code-mixing and multimodal analysis in social media promotional content remain limited. This study focused on single-image promotional posts uploaded on the official Instagram account Roti’O Indonesia. Using a qualitative descriptive approach, the study analyzed nine selected Instagram posts through purposive sampling based on the presence of code-mixing and visual promotional elements. Verbal data were analyzed through code-mixing and communicative function approaches, while visual data were analyzed using a multimodal approach. The findings indicate that insertion was the most dominant type of code-mixing used in the promotional content. The use of English in the captions is intended to construct a modern, attractive, and persuasive product image. Visual elements reinforced emotional appeal and promotional meaning. The integration of language and visual elements strengthens the process of delivering promotional messages. This study contributes to the discussion of code-mixing and multimodal discourse in digital promotion, particularly in the context of Instagram social media marketing.